The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1093/cercor/4.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Practice-related Changes in Human Brain Functional Anatomy during Nonmotor Learning

Abstract: Practice of a novel task leads to improved performance. The brain mechanisms associated with practice-induced improvement in performance are largely unknown. To address this question we have examined the functional anatomy of the human brain with positron emission tomography (PET) during the naive and practiced performance of a simple verbal response selection task (saying an appropriate verb for a visually presented noun). As a control state, subjects were asked to repeat the visually presented nouns. Areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

105
702
8
18

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,418 publications
(842 citation statements)
references
References 38 publications
105
702
8
18
Order By: Relevance
“…Another study that may at first appear to be at odds with our conclusion is a study of self-referential trait adjectives which showed an increase in ACC and a decrease in dPCC (Kelley et al, 2002). This latter study, however, more likely engaged word selection processes much as the verb generation task of Raichle et al (1994) rather than an internal self-evaluative state. The brain pattern of activation and inactivation sites supports its similarity to word generation tasks (Raichle, 2000).…”
Section: Functional Considerations: Vpcc In Ongoing Self Monitoringmentioning
confidence: 59%
“…Another study that may at first appear to be at odds with our conclusion is a study of self-referential trait adjectives which showed an increase in ACC and a decrease in dPCC (Kelley et al, 2002). This latter study, however, more likely engaged word selection processes much as the verb generation task of Raichle et al (1994) rather than an internal self-evaluative state. The brain pattern of activation and inactivation sites supports its similarity to word generation tasks (Raichle, 2000).…”
Section: Functional Considerations: Vpcc In Ongoing Self Monitoringmentioning
confidence: 59%
“…Representations in a particular brain area are said to contract (or expand) so that they can occupy a smaller (or larger) plot of neural "real estate," an effect termed "representational plasticity" (Donoghue, 1995). Practice-related changes in a wordgeneration task have been observed in a study where the prefrontal brain areas were less active in the wellpracticed automatic condition (Raichle et al, 1994). Later, Petersen et al (1998) further investigated the effects of practice on a verbal task using PET.…”
Section: Discussionmentioning
confidence: 99%
“…In go/no-go tasks, the motor response needs to be inhibited whenever a no-go trial occurs. Imaging studies reveal activation of the anterior cingulate in both of these tasks (Casey, Trainor, Orendi et al, 1997;Raichle et al, 1994).…”
Section: Executive Systemmentioning
confidence: 99%